Formulation Effects on the Mechano-Physical Properties of In Situ-Forming Resilient Hydrogels for Breast Tissue Regeneration - Daniella Goder Orbach; Meital Zilberman (Journal of Functional Biomaterials, 2024)
The need for a long-term solution for filling the defects created during partial mastectomies due to breast cancer diagnosis has not been met to date. All available defect-filling methods are non-permanent and necessitate repeat procedures. Here, we report on novel injectable porous hydrogel structures based on the natural polymers gelatin and alginate, which are designed to serve for breast reconstruction and regeneration following partial mastectomy. The effects of the formulation parameters on the mechanical and physical properties were thoroughly studied. The modulus in compression and tension were in the range of native breast tissue. Both increased with the increase in the crosslinker concentration and the polymer–air ratio. Resilience was very high, above 93% for most studied formulations, allowing the scaffold to be continuously deformed without changing its shape. The combination of high resilience and low elastic modulus is favored for adipose tissue regeneration. The physical properties of gelation time and water uptake are controllable and are affected mainly by the alginate and N-(3-dimethylaminopropyl)-N’-ethylcarbodiimide hydrochloride (EDC) concentrations and less by the polymer–air ratio. In vitro cell viability tests were performed on mouse preadipocytes and indicated high biocompatibility. The minimally invasive nature of this approach, along with the excellent properties of the scaffold, will enable the filling of complex voids while simultaneously decreasing surgical costs and greatly improving patient well-being.